Toward Sustainable Healthcare by Management Commitment, Education, and Training: Application of Proposed Guidelines in Dinas Kesehatan at the South Sulawesi Provinces in Indonesia - Julius Jillbert; Andi Ratna Sari Dewi; Najmi Kamariah; Ade Ikhlas Amal Alam (Cita konsultindo, 2023)
The need and demand for sustainable healthcare are rapidly increasing in almost every nation. In today’s world of information technology, one can no longer rely on paper or file-based manual systems. This is because all processes associated with areas like healthcare must be performed with a considerable amount of effort to keep up with the growing demands of society and the rapid increase in technology. It has become more and more necessary for every healthcare staff in a hospital to use computerized information systems for most of their daily work. Employing Nolan’s Stage Model, the present review paper tries to give suggestions to the healthcare facility at the provincial level on how to apply management commitment, education, and training.